High fat, high sucrose diet promotes increased expression of ACE2 receptor in the SIV-infected host: implications for SARS-CoV-2 infection - Delery, Elizabeth C.; Levitt, Danielle E.; Amedee, Angela M.; Molina, Patricia E.; Simon, Liz (Frontiers in Nutrition, 2024)
Introduction: People with pre-existing conditions, including metabolic comorbidities, are at greater risk for complications of SARS-CoV-2 infection and expression of machinery required for viral entry into host cells may be a contributing factor. This study tested the hypothesis that high fat, high sucrose diet (HFSD) and alcohol use increase expression of angiotensin converting enzyme 2 (ACE2) receptor and transmembrane serine protease 2 (TMPRSS2) in tissues isolated from simian immunodeficiency virus (SIV) infected macaques, the most clinically relevant model for the study of HIV. Methods: Biospecimens obtained from a longitudinal study of SIV-infected, antiretroviral therapy (ART)-treated female rhesus macaques (Macaca mulatta) were used to determine whether HFSD and chronic binge alcohol (CBA) increased ACE2 and TMPRSS2 protein and gene expression. Macaques (n=10) were assigned to HFSD or standard diet (SD) for 3 months before CBA or vehicle administration. Three months later, macaques were infected with SIV; ART was initiated 2.5 months thereafter. Tissue samples including lung, pancreas, and kidney were collected at study endpoint (12 months post-SIV infection). Results: Protein expression of ACE2 in the lung, whole pancreas, and pancreatic islets was significantly greater in HFSD-than SD-fed macaques with no significant differences in protein expression of TMPRSS2 or mRNA expression of ACE2 or TMPRSS2. CBA did not significantly alter any measures. Discussion: The increased ACE2 receptor expression observed in lung and pancreas of SIV-infected HFSD-fed female rhesus macaques aligns with reports that diet may increase susceptibility to COVID-19. These data provide direct evidence for a link between dietary quality and cellular adaptations that may increase the risk for SARS-CoV-2 infection.